What happens to the careers of European workers when immigrants "take their jobs"? - Cristina Cattaneo; Carlo V. Fiorio; Giovanni Peri (Institute for the Study of Labor (IZA), 2013)
In this paper we use a dataset that follows a representative sample of native Europeans, resident of 11 countries, over the period 1995-2001, in order to identify the effect of inflows of immigrants on their career, employment, location and wage. We use the 1991 distribution of immigrants by nationality across European labor markets to construct an imputed inflow of the foreign-born population that is exogenous to local demand shocks. We also control for a series of fixed effects that absorb individual, country-year and sector-year effects. We find that native Europeans are more likely to upgrade their occupation to one associated with higher skills and better pay, when a larger number of immigrants enter their labor market. They are also more likely to start a self-employment activity. As a consequence of this upward mobility their income increases or stays the same in response to immigration. We find no evidence of an increased likelihood to leave employment or to leave their region of residence. These effects take place within 2 years and some persist over 4 years. Hence it appears that immigrants push native European workers on a faster career track rather than reducing their employment opportunities.
Keywords: J61; O15; 330; immigrants; job upgrading; mobility; self-employment; Europe